Psychological impact on the quality-of-life in patients of psoriasis vulgaris: A systemic review - Aniruddha Ghosh,; Ambarish Ghosh,; Maidul Islam SK,; Raghav Oza, (Asian Journal of Medical Sciences, 2024)
Living with a chronic condition like psoriasis can significantly affect the individual involved. Psoriasis patients have difficulties with their physical, psychological, occupational, and social functioning. These impairments can result in psychiatric morbidity depression and anxiety disorders. This systematic review (SR) assessed the impact of psychological factors in life of psoriasis patients. The literature search comprised Medline through PubMed, Web of Science, the Cochrane Library, Wiley Online Library, and additional sources such as Google Scholar, spanning the period from 2014 to 2023. Thorough examination of the most important electronic databases was conducted. Various study designs, including observational studies, trials, and commentaries, were incorporated to ensure a comprehensive examination of the research topic. The risk of bias was evaluated using established methodology. This SR comprised 13 studies, with the Cochrane Risk of Bias Tool employed to assess biases in randomized trials across five domains. The majority of the studies demonstrated a low risk (57.69%), indicating their reliability while those categorized as unclear (37.17%) exhibited some ambiguity without compromising the validity of results. Studies categorized as high risk (5.12%) suggested significant bias and potential errors. The findings indicate an association between psoriasis and various psychological factors, including depression, anxiety, suicidal ideation, impaired emotional functioning, negative body image, and self-perception. The significant impact of depression and anxiety on individuals with psoriasis underscores the need for greater awareness of its psychological aspects. Incorporating psychological interventions into care and management strategies is crucial for addressing this chronic condition and enhancing overall well-being, thus improving quality of life.